Analysis and optimization of continuous variables quantum cryptographic systems - Pereira, Daniel Filipe Figueiredo (2023)
Quantum information theory, combined with quantum technologies, has the capacity to fundamentally alter modern society. Particularly a ected will be public classic cryptography, whose security can be e ciently cracked by a quantum computer. Continuous Variables Quantum Key Distribution (CV-QKD) presents a solution to this, allowing for provably secure communications between di ering parties to be established by providing a communication channel that is able to detect tampering attempts, all while using largely telecom-grade components. In the past couple of years, the eld of quantum cryptography has attracted more and more investment, as systems have started to reach the market. However, research in the eld is still very active, with e orts being made to both increase the system's performance, reduce costs and close security loopholes. In this PhD work we endeavoured to do just that. We begin this work by presenting an updated security proof, taking a practical approach on how the security limits may be computed numerically. We propose a novel pilot-aided, Locally generated Local Oscillator (LLO) system employing a polarization diverse heterodyne receiver. Our proposed system recovers from polarization drift exclusively through Digital Signal Processing (DSP), a choice which makes our solution experimentally simple and nancially accessible. We establish the security of our proposed system and test its resilience in a high polarization drift scenario, forced by using an electronic State of Polarization (SOP) scrambler, with the system being capable of functioning under those conditions unattended for long periods of time and being capable of generating secure keys in the asymptotic regime. We also deploy our system in a eld implementation, the rst eld trial of such a CV-QKD system in Portugal. We then proceed to explore methods for improving the performance of our previously proposed system, rst by changing from the 8-PSK constellation used previously to a 128-Amplitude and Phase Shift Keying (APSK) one. Assuming the same functioning parameters, we are able to increase performance by an order of magnitude, almost quadruple the excess noise resistance, more than triple the number of photons per symbol that can be used and reduce the number of samples necessary for functioning in the nite-size regime by 95%. We also explore methods for improving system performance by reducing the weight of the DSP. Finally, we study the impact of device imperfections on the performance and security of CV-QKD. We show that transmitter device imperfections can cause the secure key rate to be underestimated by up to 100% and that receiver device imperfections may cause secure key rate may be overestimated by 44%. Our results contribute to the advance of knowledge in the eld of CV-QKD by both improving performance, reducing costs of implementation and exploring the impact of real-word device imperfections on the theoretically derived security.